The Cognitive Approach in Learning to Read Arabic Texts: A Philosophical and Pedagogical Analysis - Ainur Rizqi Widyadhana; Aisyah Amalia Salim; Kamal Yusuf; Vera Wati Agustina (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2025)
Reading Arabic texts is a fundamental skill in mastering the Arabic language, requiring not only linguistic knowledge but also meaningful comprehension and contextual understanding. This study examines the cognitive approach to learning Arabic reading from philosophical and pedagogical perspectives. Philosophically, the analysis is grounded in classical cognitivist theories, particularly Piaget’s constructivism, Ausubel’s theory of meaningful learning, and Vygotsky’s sociocultural perspective, which emphasize active meaning construction, the role of prior knowledge, and guided learning through social interaction. Pedagogically, the study highlights the application of cognitive and metacognitive strategies such as schema activation, scaffolding, meaning elaboration, and reflective thinking within a structured reading model consisting of pre-reading, during-reading, and post-reading stages. This study employs a qualitative approach using critical literature analysis of primary and secondary sources in educational psychology and language pedagogy. The findings indicate that a cognitive-based approach supports deeper comprehension of Arabic texts, encourages reflective understanding, and facilitates meaningful learning. Moreover, the integration of cognitive strategies with Islamic educational values underscores the relevance of this approach in fostering intellectual, ethical, and reflective engagement with Arabic texts. Overall, the cognitive approach positions Arabic reading as an active and reflective learning process that bridges theoretical foundations and pedagogical practice.